THE ROLE OF NOTCH PATHWAY IN CARCINOGENESIS - M. V. Novikova; V. A. Rybko; N. V. Khromova; M. D. Farmakovskaya; P. B. Kopnin (Успехи молекулярной онкологии, 2015)
Notch transmembrane receptors family in humans consists of 4 proteins (Notch1–4) which are activated upon direct contact of cells, carrying appropriate ligands of Jagged or Dll families. This interaction leads to certain proteolytic events resulting in Notch intracellular domain translocation to the nucleus, where it activates various signaling pathways regulating the balance between cellular proliferation, apoptosis or differentiation.Proteins of the Notch family influence intraand intercellular pathways and communications of the majority of cell types. These receptors regulate both embryogenesis and adult organs and tissues homeostasis sustenance. Dysregulation of Notch signaling result in various diseases, and carcinogenesis as well. These Notch alterations are better studied in various hemoblastoses but it ,s involvement in solid tumors car- cinogenesis has recently been shown. Notch proor antioncogenic action depends not only on the type of transformed cells but also on their microenvironment.This review is dedicated to canonical Notch signaling, as well as to non-canonical actions, epigenetic regulation and current proand antioncogenic functions in human malignancies. Special attention is drawn to interaction between Notch and other signaling pathways controlling epithelia-to-mesenchyma transition of cells, stem cells formation, sustention of specific niches, cellular differentiation, angiogenesis both during embryogenesis and in pathological conditions. Pharmacological regulation of Notch activation could be a promising way of anticancer therapy.